THE EFFECT OF LIQUIDITY, INCOME DIVERSIFICATION, OPERATIONAL EFFICIENCY, CREDIT RISK, AND LEVERAGE ON THE STABILITY OF REGIONAL DEVELOPMENT BANKS (BPD) IN INDONESIA: PERIOD 2021–2025 - Nova Fernita S; Erlina; Rina Br Bukit (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Regional Development Banks (BPD) play a strategic role as intermediary institutions supporting regional economic development and maintaining the stability of the regional financial system. Therefore, the ability of BPDs to maintain financial stability is a crucial aspect to ensure the sustainability of their intermediation function and increase their contribution to the regional economy. This study aims to analyze the effect of internal bank factors, including liquidity, revenue diversification, operational efficiency, credit risk, and leverage, on the stability of Regional Development Banks in Indonesia. This study uses a quantitative approach with secondary data obtained from the annual financial reports of 24 Regional Development Banks for the period 2021–2025. Data analysis was conducted using panel data regression with a Random Effects Model (REM) approach. The results show that revenue diversification and operational efficiency have a positive and significant effect on BPD stability, while credit risk has a negative and significant effect on BPD stability. Meanwhile, liquidity and leverage do not significantly affect BPD stability. These findings indicate that BPDs' ability to expand revenue sources, improve operational efficiency, and control credit risk is a more decisive factor in maintaining stability than liquidity management and funding structure. This study provides empirical evidence regarding the determinants of BPD stability in Indonesia and enriches the literature on regional banking stability. In addition, the research results are expected to be used as consideration for BPD management and regulators in formulating policies that support strengthening the resilience and sustainability of the regional banking industry.